Business, ethics and peace - Bouckaert, Luk, 1941-; Chatterji, Manas, 1937- (Contributions to conflict management, peace economics and development ;, 2015)
Good business needs a peaceful and just world in which to operate and prosper. Likewise, peace thrives in a healthy economic environment. However, many companies - either directly or indirectly - are involved in the arms race and in a battle to exploit and control scarce resources. As a result of the ambiguous power of business, a timely reflection on its impact on war and peace is needed as well as a conscious pro-peace commitment. Business, Ethics and Peace gathers a selection of papers presented at the International SPES Conference Business for Peace, Strategies for Hope at Ypres, April 10-12, 2014. Among the many initiatives commemorating the centennial of World War I, this project focuses on the ethical need to prevent the next conflict. It interprets and presents peace as a holistic and evolving concept, defining the need for an ethical charter of human rights and responsibilities. The papers illustrate the impact of religion in peace management and present solutions and practices for corporate peace-building.